Sosialisasi Keuangan Modern: Mengenalkan Konsep Investasi Saham Syariah Melalui Stocklab di MTs Hidayatul Muta'alimin Sidoarjo - Norma Rosyidah (Ngabekti: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program aims to enhance Islamic financial literacy and introduce capital market concepts to students at MTs Hidayatul Muta'alimin. Conventional financial education often feels abstract and complex for middle school students. To address this, the program implemented a gamification method using the Stocklab board game as an interactive learning tool. The socialization involved interactive presentations, guided simulation gameplay, and a mini-tournament to foster enthusiasm. Data collection through pre-tests, post-tests, and observations showed a significant increase in students' understanding of Sharia stock investment, financial management, and capital market mechanisms. Furthermore, the experiential learning approach successfully stimulated students' interest in becoming future sharia investors. This program demonstrates that game-based learning is an effective and engaging alternative for early financial education in Islamic school environments.